Effect of Friction Stir Welding Parameters with Newly Developed Tool for Lap Joint of Dissimilar Polymers. (2015) - Eslami, Shayan; Ramos, Tiago; Tavares, Paulo J.; Moreira, P.M.G.P.
Abstract: Friction stir welding (FSW) is relatively a new welding method where heat generated by friction is used to forge components together under an axial force. In this method, the generated heat does not exceed the material melting point, instead, the material is heated to its forging temperature and is stirred together by a rotating tool. Since the invention of FSW, this technique has been mainly used for welding aluminium plates together for butt and lap joint configurations. This study is focused on welding lap joint of dissimilar polymers with a new developed tool, in order to evaluate the effect of the welding parameters on the weld strength. This paper describes the process of developing a stationary FSW tool for welding thin plates of polypropylene and polyethylene. The welds produced with this tool improved the welds surface quality and strength significantly. The use of the proposed tool showed to improve the stability in the axial force magnitude during the welding procedure in comparison with a conventional FSW tool. It was also concluded that the rotational and traversing speed have the most effective role regarding the overall specimen tensile strength. Moreover, unlike lap joint of metallic materials, the defect occurred in the retreating side of the welds.